Effect of five years of notillage and mulch on soil properties and tuber yield of cassava on an acid Ultisol in southeastern Nigeria - Hulugalle, N.R.; Lal, R.; Gichuru, M. (Cambridge University Press, 1990)
The effect of no-tillage and mulch on soil properties and tuber yield of cassava was studied over a five year period on an infertile, acid Ultisol in south-eastern Nigeria. Mulch was applied at a rate of 12 t ha−1 as a split application once at planting and once six months after planting. No chemical fertilizers were used during the trial. Bulk density and proportion of micropores (pore radius, r, <1.4 µm) were greater, and proportion of macropores (r>14.4 µm) lower, with no-tillage. Water infiltration was increased by mulching, being greatest in tilled, mulched plots. Soil chemical properties were not significantly affected by tillage system, although levels of exchangeable calcium, magnesium and potassium were higher and acid saturation lower with mulching. Soil physical and chemical properties were best with tillage and mulching, and poorest when neither tillage nor mulch was used. Cassava tuber yield was unaffected by tillage system but increased by mulching.